Analisis Pengaruh Minat Pengunjung Wisata Bukit Cinangkiak - Ida Nirwana; Rasidah Nasrah; Regina Rahmahayati (CV. Ulil Albab Corp, 2024)
The interest of visitors in a tourist attraction can determine the quality of the services provided and the various factors that shape their behavior. Among these factors are the image and promotion of the destination. The image of a destination in a tourist spot can serve as a catalyst for the attraction of the tourist spot itself; promotion aims to convince consumers to utilize the provided services or products, and it can boost and enhance tourist visits by ensuring their satisfaction. Bukit Cinangkiak Tourism in West Sumatra Province conducted this research. The purpose of this study was to determine the effect of destination image and promotion on visitor interest. The accidental sampling method relies on chance, allowing anyone who unintentionally encounters the researcher to serve as a sample. Therefore, the researcher will select 100 individuals from the current population of 7,463 as samples or respondents. The data collection method uses a questionnaire. The study's findings indicated that destination image and promotion have a positive relationship with visitor interest. The study found that both Destination Image and Promotion partially influence Visitor Interest. The coefficient of determination (R2) yielded a value of 0.097, indicating a 9.7% contribution from the variables of destination image and promotion, with other variables exerting a 90.3% influence.